The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2166/wpt.2022.024
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and toxicological assessment of selected active pharmaceutical ingredients in effluents of pharmaceutical manufacturing plants and wastewater treatment plants in Kampala, Uganda

Abstract: There is an increasing eco-toxicological risk associated with pharmaceuticals globally. The prevalence of six active pharmaceutical ingredients (APIs) was studied in effluents of three pharmaceutical manufacturing plants (PMPs) and two wastewater treatment plants (WWTPs) in Kampala, Uganda to ascertain the removal potentials for APIs. The APIs include atenolol, losartan, carbamazepine, sulfamethoxazole, clarithromycin, and diclofenac. The APIs were extracted using solid-phase extraction cartridges and concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Similarly, the presence various chemicals, including pesticides (27,46), perfluorinated alkylated substances (PFAS) (47), personal care products (39), and persistent organic pollutants (POPs) (36), has been documented in surface waters, with concentrations exceeding regulatory limits in some cases, indicating potential risks to agricultural productivity and human health (19,38,48). Their contamination poses a significant public health concern as it can be detrimental to freshwater resources, similar to the concerns raised in previous studies (38).…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…Similarly, the presence various chemicals, including pesticides (27,46), perfluorinated alkylated substances (PFAS) (47), personal care products (39), and persistent organic pollutants (POPs) (36), has been documented in surface waters, with concentrations exceeding regulatory limits in some cases, indicating potential risks to agricultural productivity and human health (19,38,48). Their contamination poses a significant public health concern as it can be detrimental to freshwater resources, similar to the concerns raised in previous studies (38).…”
Section: Introductionmentioning
confidence: 62%
“…To date, several studies have been conducted in Uganda to investigate the presence and concentrations of emerging pollutants in different environmental systems in Uganda for example in water (27,28), sediments (27,29), surface waters (30)(31)(32), food crops (33,34), edible insects (35), breastmilk (36) and in fish (30). These studies have identified a range of compounds, including pharmaceutical residues (e.g., antibiotics, analgesics) (26,37,38), personal care products (e.g., fragrances, UV filters) (39), pesticides (e.g., herbicides, insecticides) (27,35,40,41), industrial chemicals (e.g., flame retardants, plasticizers) (36,39,42), microplastics and heavy metals (43)(44)(45). The concentrations of emerging pollutants reported in the literature vary depending on the sampling location, environmental matrix, and analytical techniques used.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations